Early Ground‐Based Work by Auroral Pioneer Carl Størmer on the High‐Altitude Detached Subauroral Arcs Now Known as “STEVE” - Michael Hunnekuhl; Elizabeth MacDonald (Space Weather)
Abstract STEVE (Strong Thermal Emission Velocity Enhancement) phenomenon related structures have received much attention from space weather audiences in recent years. MacDonald et al. (2018, https://doi.org/10.1126/sciadv.aaq0030), reports on a link between these ionospheric structures and the subauroral ion drift for the first time. This commentary summarizes previously overlooked observations of a distinct type of detached subauroral arc by the aurora pioneer Carl Størmer in Norway between 1911 and 1940, including coordinated simultaneous multistation‐based altitude measurements. This commentary points out that his phenomenological descriptions and height measurements show a striking resemblance to modern descriptions and measurements of STEVE.